Let your students cheat on mathematics online exams: students’ perspectives - Erdawati Nurdin; Zubaidah Amir MZ; Hayatun Nufus; Deepti Thakur; Firdous A. Shah; Rakesh Dube; Tommy Tanu Wijaya (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
The Covid-19 outbreak has an impact on the provision of education. One of them is the process of online assessment or examination. Difficulties occur during online exams; weak supervision can increase cheating behavior among students. Generally, teachers or lecturers think about how to prevent this behavior. However, what if they are allowed to